Environmental enrichment in murine models and its translation to human factors improving conditions in alzheimer disease - Colavitta, María Florencia (2023)
Fil: Colavitta, María Florencia. Pontificia Universidad Católica Argentina. Facultad de Psicología y Psicopedagogía. Centro de Investigaciones en Psicología y Psicopedagogía; Argentina